The relationship between developing talent and job satisfaction in selected public universities - Lukman@Zawawi, Mohamad; Kamal, M.Y. (2017)
In any organizations, Developing Talent (DT) is essential. Theoretically, employees will be developed parallel with their years of contribution to the institutions. Indirectly, their Job Satisfaction (JS) will be achieved. DT has become part of the main agenda to Ministry of Higher Education (MOHE) to ensure the development of talent is continuous. Therefore, this research will investigate the relationship between DT and JS in selected public universities in Malaysia. Quantitative approach has been used in order to collect primary data from 238 respondents in selected public universities. Information obtained from this method has been analyzed using IBM Statistical Package Social Sciences (SPSS). As a result, there was a moderate relationship recorded between DT and JS. However, University A scored slightly higher correlation between DT and JS as compared to other two public universities. As a conclusion, each public university has their own way in order to develop their talent according to the mission and vision of the university and directly will achieve JS of each employee in the organization.